Drama in the EFL Classroom: Critical Review of the Literature - Ilyas, Hamzah Puadi (Journal of ELT Research, 2016)
This article presents critical review of three empirical studies on the use of drama in language learning. Results of those studies are very supportive to integrate drama into EFL. Also, the results of the studies are in agreement with the ideas stating that drama can give positive contributions to students’ language proficiency. In fact, apart from improving students’ language skills, drama can promote collaboration and negotiation. Given the advantages of using drama in the EFL classroom shown by those studies, there is little information concerning the use of drama in the Indonesian EFL.